2003
DOI: 10.1021/ja0347538
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Asymmetric Bio- and Chemocatalytic Synthesis of Saccharides − Stereoselective Formal O-Glycoside Bond Formation Using Palladium Catalysis

Abstract: A novel integrated bio- and chemocatalytic approach to the de novo catalytic asymmetric synthesis of saccharides has been developed. Acetoxypyranones obtained enantiopure by enzymatic resolution have been shown to undergo highly stereoselective palladium-catalyzed formal O-glycoside bond formation. The combination of these protocols can be applied to the iterative asymmetric catalytic synthesis of saccharides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…Much effort has also been directed towards a conceptually different glycosylation method, namely, the de novo synthesis of glycosides, although this method was investigated extensively and successfully many years ago. [310] In recent studies, [311] the glycoside bonds were constructed through palladium-catalyzed allylation, and the anomeric configuration could be controlled by the reagent rather than by anomeric or neighboring-group effects. The glycosylation usually proceeded in a highly stereoselective manner without the use of Lewis acid promoters, and the products could be elaborated readily to furnish natural or non-natural carbohydrates.…”
Section: Other Aspectsmentioning
confidence: 99%
“…Much effort has also been directed towards a conceptually different glycosylation method, namely, the de novo synthesis of glycosides, although this method was investigated extensively and successfully many years ago. [310] In recent studies, [311] the glycoside bonds were constructed through palladium-catalyzed allylation, and the anomeric configuration could be controlled by the reagent rather than by anomeric or neighboring-group effects. The glycosylation usually proceeded in a highly stereoselective manner without the use of Lewis acid promoters, and the products could be elaborated readily to furnish natural or non-natural carbohydrates.…”
Section: Other Aspectsmentioning
confidence: 99%
“…811 2,3-Unsaturated pyranosides can also be synthesized de novo by the Pd-catalyzed acetalization of chiral pyranones followed by post-glycosylative reduction and dihydroxylation to produce three additional stereocenters in the newly formed hexose unit. 12,13 Similarly, 3,4-dideoxyhexenosides have been converted into S -linked disaccharides and glycoconjugates via epoxidation and S N 2 ring-opening. 14 …”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, three groups have independently reported the application of the Tsuji-Trost reaction to the construction of glycoside bonds [181]. These transformations proceed with good levels of stereocontrol and allow for catalyst-based control of anomeric stereochemistry (eq 118) [181c].…”
Section: Heterocycle Synthesis Via the Tsuji-trost Reactionmentioning
confidence: 99%